-f(x) reflects f(x) over the x-axis
f(x) - a translates f(x) a units down.
f(x + b) translates f(x) b units to the left
1) Given f(x) = x², then g(x) = -f(x) = -x² is the graph of g(x) that has been reflected over the x-axis.
2) Given the function: h(x) = -x², then g(x) = h(x) - 4 = -x² - 4 is the equation for the graph of g(x) that has also been shifted down 4 units.
3) Given the function: k(x) = -x² - 4, then g(x) = k(x + 1) = -(x+1)² - 4 is the equation for the graph of g(x) that has been shifted left 1 unit.